Self-concealment, discrimination, and mental health in Macedonia: Disparities experienced by sexual and gender minorities. Issue 8 (3rd August 2019) - Zhou, Sasha; King, Elizabeth J.; Gjorgiovska, Jovana; Mihajlov, Antonio; Stojanovski, Kristefer
ABSTRACT: While sexual and gender minorities (SGM)-based discrimination and poor mental health is well established in the literature within Western contexts, there is a significant gap in our understanding in other regions, specifically Southeastern Europe. Additionally, limited information exists on self-concealment's role in these pathways. We explored the relationship between self-concealment, discrimination and mental health in Macedonia, a country rife with sociopolitical oppression towards the population. We utilised regression and structural equation models to identify the effects of self-concealment on the relationship between discrimination and rumination and social interaction anxiety from a cross-sectional survey of 18–30 year olds ( n  = 396). Self-concealment was a significant mediator between discrimination and psychosocial outcomes; accounting for 29% of the effect from discrimination to social anxiety, and 57% of the effect from discrimination to rumination ( p  < .001). Results reveal that by actively managing their identity, SGM in Macedonia experience elevated distress beyond the impact of discrimination. The results discern salient information on how to disrupt the adverse role of discrimination of SGM on mental health outcomes. This provides a crucial template for the global public health community when developing mental health programmes and advocating for policies, to begin reversing the mental health inequities created within the country.